The New Paradigm for Social Studies Learning in Junior High Schools - Muhammad AQil (Yayasan Insan Mulia Bima, 2023)
A new paradigm in social studies education needs to be implemented as an effort to enhance the quality of the educational process and meet the evolving societal demands for education. Consequently, innovations in social studies education can be effectively carried out when guided by the results of evaluations and research in the field of social studies education. Learning can be conducted within collaborative study groups, emphasizing group-based learning. Until now, this approach has not been intentionally developed within the instructional process, hence presenting a challenge and a demand for educational innovation. Once implemented, it will be capable of addressing the shortcomings of the instructional methods that have been applied in educational institutions.